2010
DOI: 10.1007/s12098-010-0194-y
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion of Blood and Components in Critically Ill Children

Abstract: The physicians prescribing transfusions must have a thorough understanding of the various blood products, their indications and contraindications, and requirements for modification of the blood products to prevent probable adverse effects. Decision to give an RBC transfusion should not be based solely on Hb concentration, it should take in account high severity of illness; active bleeding; emergency surgery; etc. Using restrictive transfusion strategy of transfusion RBCs can decrease transfusion requirements w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Although several studies looked at the spectrum of coinfections reported with UTIs, none investigated exclusively for diarrhea 12,13 . Conversely, there are a number of cohort and case control studies of children presenting with diarrhea that specifically studied the incidence of associated culture-proven UTIs 14–23 . In addition, 2 studies were discovered during our review of the literature that included reports of diarrhea in children diagnosed with UTIs.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies looked at the spectrum of coinfections reported with UTIs, none investigated exclusively for diarrhea 12,13 . Conversely, there are a number of cohort and case control studies of children presenting with diarrhea that specifically studied the incidence of associated culture-proven UTIs 14–23 . In addition, 2 studies were discovered during our review of the literature that included reports of diarrhea in children diagnosed with UTIs.…”
Section: Discussionmentioning
confidence: 99%